An ecosystem approach to health and its applications to tropical and emerging diseases - David Waltner-Toews
Disease and health outcomes occur within a complex socio-ecological context characterized by feedback loops across space and time, self-organization, holarchies, and sudden changes in organization when thresholds are reached. Disease control programs, even if they are successful, may undermine health; conversely, programs in agriculture and economic development designed to improve health may simply alter disease patterns. A research and development strategy to promote sustainable health must therefore incorporate multiple scales, multiple perspectives, and high degrees of uncertainty. The ecosystem approach developed by researchers in the Great Lakes Basin meets these criteria. This has implications for community involvement in research, development policies, and for understanding and controlling tropical and emerging diseases. Even if unsuccessful in achieving specific outcome targets, however, the requirements of this approach for open and democratic communication, negotiation, and ecological awareness make its implementation worthwhile.